Characteristics of the active clinical trials developed in the Social Health Security of Peru - Soto-Ordoñez, Suly (2022)
Objetive: To describe the characteristics of active clinical trials (CTs) developed in the Social Health Security of Peru. Material and methods: Observational and descriptive study of active CTs between May 24 to July 8, 2021, registered in the Peruvian Registry of Clinical Trials during the period 2007-2020. The distribution of the different variable was analyzed, such as the number of CTs, phase, EsSalud networks, sponsor, funding sources, specialty, number of EsSalud research centers per CT, CIEI that approved CT by research center, and the calculation of relative and absolute frequencies. Results: 97 active CTs were identified, executed 144 times in 23 different research centers that belong to EsSalud. 94.9% of the active CTs were sponsored by pharmaceutical industries and 36% belong to the specialty of oncology. 80.42% are phase III and 70.8% were approved by an EsSalud CIEI. Conclusions: The active CTs in EsSalud are developed mostly in Lima, are financed by the pharmaceutical industry and are mostly approved in the CIEI of EsSalud.